2008
DOI: 10.1085/jgp.200810051
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Inner Pore Region of TRPV1 Channels Revealed by Block with Quaternary Ammoniums

Abstract: The transient receptor potential vanilloid 1 (TRPV1) nonselective cationic channel is a polymodal receptor that activates in response to a wide variety of stimuli. To date, little structural information about this channel is available. Here, we used quaternary ammonium ions (QAs) of different sizes in an effort to gain some insight into the nature and dimensions of the pore of TRPV1. We found that all four QAs used, tetraethylammonium (TEA), tetrapropylammonium (TPrA), tetrabutylammonium, and tetrapentylammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 72 publications
(105 reference statements)
2
39
0
Order By: Relevance
“…This picture showed that the TRPV1 channel shares many structural features with other ion channels of known structures, such as the voltage-gated Kv1.2 channel and the Kv1.2-2.1 paddle chimera (Long et al, 2005a(Long et al, , 2007. The TRPV1 channel structure supported previous studies proposing that the TRPV1 channel is assembled as a tetramer (Kedei et al, 2001;Kuzhikandathil et al, 2001) and confirmed functional studies showing that the channel pore and corresponding intracellular activation gate(s), formed by the S5 to S6 transmembrane segments, exist along the tetramer axis of symmetry (Oseguera et al, 2007;Jara-Oseguera et al, 2008;Salazar et al, 2009). The TRPV1 structure shows that a peripheral domain in each subunit, encompassing S1-S4 segments, is connected to the pore by a short linker, a feature also conserved in voltagedependent potassium channels (Long et al, 2005a).…”
Section: Introductionsupporting
confidence: 75%
“…This picture showed that the TRPV1 channel shares many structural features with other ion channels of known structures, such as the voltage-gated Kv1.2 channel and the Kv1.2-2.1 paddle chimera (Long et al, 2005a(Long et al, , 2007. The TRPV1 channel structure supported previous studies proposing that the TRPV1 channel is assembled as a tetramer (Kedei et al, 2001;Kuzhikandathil et al, 2001) and confirmed functional studies showing that the channel pore and corresponding intracellular activation gate(s), formed by the S5 to S6 transmembrane segments, exist along the tetramer axis of symmetry (Oseguera et al, 2007;Jara-Oseguera et al, 2008;Salazar et al, 2009). The TRPV1 structure shows that a peripheral domain in each subunit, encompassing S1-S4 segments, is connected to the pore by a short linker, a feature also conserved in voltagedependent potassium channels (Long et al, 2005a).…”
Section: Introductionsupporting
confidence: 75%
“…Taken together, the data available to date indicate that QAs may act as permeant blockers of TRP channels. Consistent with this possibility, TEA and TMA displayed strong voltage-dependent relief of inhibition at Ϫ25 mV compared with that at Ϫ60 mV, similar to the extracellular open channel block of voltage-gated potassium channels and intracellular pore block in TRPV1 channels by other QAs (Jara- Oseguera et al, 2008).…”
Section: Extracellular Quaternary Ammonium Block Of Trpv1mentioning
confidence: 54%
“…We thus believe that although the specific drug-receptor affinity may change depending on the expression system (Lev et al, 2012), the observation of QA blockade will be universal, regardless of the cell system used. This notion is further supported by the observation that LAs and QAs can block TRPV1 in mammalian cells (Oseguera et al, 2007;Jara-Oseguera et al, 2008;Leffler et al, 2008).…”
Section: Extracellular Quaternary Ammonium Block Of Trpv1mentioning
confidence: 71%
See 2 more Smart Citations